PERANCANGAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) ATAP ON-GRID DI KANDANG AYAM CLOSED HOUSE UNIVERSITAS UDAYANA - Rose, D. J.; Setiawan, I N; Santiari, D. A. S. (Jurnal SPEKTRUM, 2025)
The fulfillment of electricity needs in Indonesia is still dominated by fossil fuel power plants, while the potential for solar energy in Indonesia is very large to be developed. Udayana University's Closed House Chicken Coop, as a broiler chicken coop with a closed system, requires a continuous supply of electricity to maintain the ideal temperature. This study aims to evaluate the design of rooftop Solar Power Plants (PLTS) as an alternative energy solution that can meet the electricity needs of households during the day. The design was carried out using HelioScope software with two scenarios: (1) the optimal angle of 14.66° and (2) the real slope angle of the roof of 8°. Both scenarios use 34 solar modules and one inverter with a power of 17 kW, with a potential power capacity of 14.5 kWp. The simulation results show that scenario 1 has an annual energy production of 25.04 MWh and is able to supply 31% of the total electricity demand, while scenario 2 produces 23.33 MWh and supplies 29% of the electricity demand. Therefore, scenario 1 is a more optimal design option for the implementation of rooftop solar power in this chicken coop.